Influence of some factors on the potato crossing success - Khashbaatar, Nyamgerel; Yadamsuren, Myagmarsuren (Mongolian Journal of Agricultural Sciences, 2022)
Potatoes are the second most important crop in Mongolia, ranking only after wheat. Since 2012, researchers and farmers have begun using a more conventional hybridization technique in potato breeding. The field experiment was conducted at Institute of Plant Agricultural Science during 2014-2021. This study was carried out to determine the effect of some factors on the potato breeding success. The crosses were made in the greenhouse. One hundred ninety-five different crosses were made between 47 parent cultivars. The results show that crossing success ranged from 7.5 to 47.8 percent and averaged 26.7 %. The crossing success heavily depends upon environmental conditions and parental genotypes. The parental genotypes showed a dominance effect during the crossing success. According to research, the crossing success was positively correlated with a rainfall during the crossing period, and negatively correlated to that day’s temperature. In order to determine the effects of parental materials separately, we analyzed 17 cultivars which are used in crossing both female and male parents. The crossing success was 25.2 % for females and 21.3 % for males. The cultivar Leandra, Kuroda, Solist, Elfe and CIP390478.9 displayed the highest value compared to their male parent, while the male components Atar-1, Primadonna, Anushka, Bellarosa and D-11-01-48 displayed higher values when compared to the female parent. Furthermore, the variety Gala, Quarta, Patricia and Ewelina can be used an efficient as a both parents. Төмсний эрлийзжүүлгийн үр тогтолтын амжилтанд үзүүлэх хүчин зүйлсийн нөлөөг судалсан дүн Хураангуй Судалгаа явуулсан жилүүдэд нийтдээ 195 хослолоор эрлийзжүүлэг хийгдсэнээс 116 хослол буюу 56.5 хувьд нь үр тогтсон байна. Төмсний ургамлын эвцэлдүүлэгийн үр тогтолтын амжилт нь 7.5-47.8 %-ийн хооронд хэлбэлзэж дунджаар 26.7 % байв. Үр тогтолтын амжилт нь эвцэлдүүлэг хийх үеийн цаг агаарын нөхцөл, эх, эцэг хослол буюу генотипын шинж чанараас хамаарч ихээхэн ялгаатай байна. Үр тогтолтын амжилт нь тухайн хугацааны температуртай сөрөг, тунадастай эерэг хамраалтай байгааг илрүүлэв. Судалгааны жилүүдэд эвцэлдүүлэгт ашиглагдсан эх, эцэг хэлбэрүүдийн үр тогтолтын амжилтыг тус бүрт нь тооцож үзэхэд эх хэлбэрээр ашиглахад үр тогтолтын амжилт дунджаар 25.2 %, эцэг хэлбэрийнхэд 21.3 % байна. Леандра, Курода, Солист, Эльф, CIP390478.9 зэрэг сортуудыг эвцэлдүүлэгт эхээр ашиглахад тэдгээрийн үр тогтолтын амжилт эцгээр ашигласнаас дунджаар 10-30 хувиар илүү байгаа бол, Атар-1, Примадонна, Анушка, Беллароза, Д-11-01-48 сортуудыг эцэг хэлбэрээр ашиглахад үр жимс үүсэлт буюу үр тогтолтын амжилт өндөр байна. Харин Гала, Куарта, Патрица, Эвэлина зэрэг сортуудыг эвцэлдүүлэгт эх, эцгийн аль ч хэлбэрээр ашиглах боломжтой нь судалгаагаар тогтоогдлоо. Түлхүүр үг: төмс, эвцэлдүүлэг, сорт, генотип, эрлийзжүүлэг